Evaluative Language in Lithuanian Students’ English Writing. A Study of ‘Important’ and ‘Interesting’ - Bikelienė, Lina (Respectus Philologicus, 2016)
Critical thinking, as one of the competences to be developed at universities, requires the ability to evaluate. Though different parts of speech can fall under the category of evaluative language, adjectives are among the most frequently used means to express evaluation. The present study is limited to the use of two positive evaluative adjectives in Lithuanian learner English. It aims to analyse whether the use of “interesting” and “important” in Lithuanian students’ writing depends on the text genre, language proficiency, educational institution variables and whether it differs in NNS and NS writing. The data were obtained from the Lithuanian parts of the Corpus of Academic Learner English and the International Corpus of Learner English, the corpus of the first year students’ examination essays written at Vilnius University and comparable native English corpora. The results of the study indicate overuse of “important” and “interesting” in Lithuanian students’ corpora and highlight the different roles that the variables under consideration play in the use of the studied adjectives.